Speaking for Success - Miculka, Jean H. (Cengage Learning, Inc, 1999)
This activity-oriented text is designed to develop and reinforce the skills necessary for success in a variety of interpersonal communication and public speaking situations. Literature selections and workplace cases show the importance of effective communication strategies in professional and social contexts